2020
DOI: 10.3390/ani10061073
|View full text |Cite
|
Sign up to set email alerts
|

Color of Colon Content of Normal and Intrauterine Growth-Restricted Weaned Piglets Is Associated with Specific Microbial Taxa and Physiological Parameters

Abstract: A well-balanced gut microbiome is associated with improved health outcomes, but to date, the GM of IUGR piglets have only been sparsely investigated. Here, we investigated GM composition, color of colon content, and blood parameters of 20 IUGR and 20 normal 24-day-old piglets. No significant differences were detected in colon microbiota composition between IUGR and the normal piglets with respect to alpha and beta diversity measures. The colon content of these piglets displayed three colors: brown, black, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In the present study, IUGR increased plasma and colonic mucosa DAO and D -lactate concentrations, which is in accordance with a previous report [ 26 ]. Indeed, IUGR can deteriorate hindgut epithelial barrier function in piglets during development [ 27 ]. Dietary BA supplementation to NBW and IUGR piglets decreased plasma DAO concentration in the NBW piglets and plasma and colonic D -lactate, DAO, and endotoxin concentrations in the IUGR piglets.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, IUGR increased plasma and colonic mucosa DAO and D -lactate concentrations, which is in accordance with a previous report [ 26 ]. Indeed, IUGR can deteriorate hindgut epithelial barrier function in piglets during development [ 27 ]. Dietary BA supplementation to NBW and IUGR piglets decreased plasma DAO concentration in the NBW piglets and plasma and colonic D -lactate, DAO, and endotoxin concentrations in the IUGR piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that intestinal microbiota, diversity, and metabolite profiles of IUGR piglets were significantly different from those of normal weight piglets, suggesting that gut microbes are potentially associated with impaired growth and development [ 16 , 17 , 18 , 19 ]. In rats, IUGR induces changes in the intestinal microbiota composition, and these changes persist throughout life [ 10 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the organ weights of piglets suffering IUGR are significantly lower compared with normal piglets [ 1 ]. Additionally, IUGR piglets show signs of gut adaptation delay, altered microbiota, and intestinal disease [ 13 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%